Jean Rouch. - Boutang, Pierre-André, 1937-2008; Rouch, Jean, 1917-2004; Surugue, Bernard; Leboutte, Patrick, 1960-; Riolon, Luc, 1959-; Roudil, Marc-Antoine, 1958- (Geste cinématographique, 2005)
Presents ten films by ethnologist Jean Rouch, along with interviews of the filmmaker, famous for his Niger-based films